INTERPERSONAL MEANING IN THE SHORT STORIES OF WILLEM ISKANDER’S SI BULUS-BULUS SI RUMBUK-RUMBUK - ULFA YOZA SALSABILA; ELIA MASA GINTING; WILLEM SARAGIH (LINGUISTICA, 2021)
This study aimed to analyze the mood and modality used in the short stories of Willem Iskander’s Si Bulus-Bulus Si Rumbuk-Rumbuk, elaborating and explaining the interpersonal meaning realized in each short story. The source of data was taken from a book authored by Willem Iskander, entitled “Si Bulus- Bulus Si Rumbuk-Rumbuk”. This research showed that : (1) there were 157 clauses in the short stories with three mood types and two degrees of modality. (2) interpersonal meaning is realized based on the order of the subject and the finite. (3) the reason why the interpersonal meaning is realized in the way they are is that the author wants to share his thoughts and experiences of Mandailingnese by classifying each clause and finding the dominant use of declarative mood as the most direct and soft way of conveying the author’s thought